1998
DOI: 10.1016/s0266-7681(98)80207-6
|View full text |Cite
|
Sign up to set email alerts
|

What is Cold Intolerance?

Abstract: There are four types of symptoms on exposure to cold in the condition known as cold intolerance: pain/discomfort, stiffness, altered sensibility and colour change. They may occur in isolation or in any combination. Symptoms were present in at least 64% of 200 patients 24 months after hand injury. Pain was found to be the most troublesome symptom. Colour change in the digits was regarded by patients as the least troublesome symptom. Symptoms may begin immediately after injury, but are more likely to develop wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 5 publications
2
64
0
3
Order By: Relevance
“…86,87,[89][90][91][92][93][94][95][96][97][98][99][100] Several studies have supported the continuation of cold-sensitivity symptoms in patients with hand injuries and nerve injuries and following replantation. 89,91,92,97,101,102 Campbell and Kay evaluated 176 patients following hand injuries, 73% of whom reported cold-related symptoms; most of these were related to pain. 91 Graham and Schofield evaluated patients more than 2 years after hand injury; 86 most of these patients (90% of trauma cases) reported cold intolerance, and only 9% reported an improvement over time.…”
Section: Considerations Of Cold Sensitivity and Contextual (Psychosocmentioning
confidence: 99%
See 1 more Smart Citation
“…86,87,[89][90][91][92][93][94][95][96][97][98][99][100] Several studies have supported the continuation of cold-sensitivity symptoms in patients with hand injuries and nerve injuries and following replantation. 89,91,92,97,101,102 Campbell and Kay evaluated 176 patients following hand injuries, 73% of whom reported cold-related symptoms; most of these were related to pain. 91 Graham and Schofield evaluated patients more than 2 years after hand injury; 86 most of these patients (90% of trauma cases) reported cold intolerance, and only 9% reported an improvement over time.…”
Section: Considerations Of Cold Sensitivity and Contextual (Psychosocmentioning
confidence: 99%
“…89,91,92,97,101,102 Campbell and Kay evaluated 176 patients following hand injuries, 73% of whom reported cold-related symptoms; most of these were related to pain. 91 Graham and Schofield evaluated patients more than 2 years after hand injury; 86 most of these patients (90% of trauma cases) reported cold intolerance, and only 9% reported an improvement over time. Long-term cold intolerance in patients with hand injuries was evaluated by Nancarrow et al; 97 69% of patients reported cold intolerance, and 97% of these patients continued to have symptoms 5 years after injury.…”
Section: Considerations Of Cold Sensitivity and Contextual (Psychosocmentioning
confidence: 99%
“…Pain may also be associated with cold sensitivity 15,27,28,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity. Many studies have demonstrated persistent cold sensitivity and substantial pain following hand trauma 65,66,68,71,76,79 . Cold sensitivity remains a challenge following peripheral nerve injury, particularly for patients who reside in cold environments.…”
Section: Discussionmentioning
confidence: 99%
“…• • cold intolerance -described using an existing scale (Campbell and Kay, 1998); • • loss of flexion -defined as a fingertip pulp to distal palmar crease distance over 10 mm on active flexion; • • infection -defined as patient recall of the need for at least one postoperative course of antibiotics that was not prescribed as prophylaxis;…”
Section: Adverse Outcomesmentioning
confidence: 99%